Robustness and Stability Analysis of a Predictive PI Controller in WirelessHART Network Characterised by Stochastic Delay - Sabo Miya Hassan; Rosdiazli Ibrahim; Nordin Saad; Vijanth Sagayan Asirvadam; Kishore Bingi; Tran Duc Chung (International Journal of Electrical and Computer Engineering (IJECE), 2017)
As control over wireless network in the industry is receives increasing attention, its application comes with challenges such as stochastic network delay. The PIDs are ill equipped to handle such challenges while the model based controllers are complex. A settlement between the two is the PPI controller. However, there is no certainty on its ability to preserve closed loop stability under such challenges. While classical robustness measures do not require extensive uncertainty modelling, they do not guarantee stability under simultaneous process and network delay variations. On the other hand, the model uncertainty measures tend to be conservative. Thus, this work uses extended complementary sensitivity function method which handles simultaneously those challenges. Simulation results shows that the PPI controller can guarantee stability even under model and delay uncertainties.